2011
DOI: 10.3233/jad-2011-100999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Newly Developed Cognitive Intervention in Amnestic Mild Cognitive Impairment and mild Alzheimer's disease: A Pilot Study

Abstract: Recent studies have shown that patients with Alzheimer's disease (AD) and its possible prodromal stage mild cognitive impairment benefit from cognitive interventions. Few studies so far have used an active control condition and determined effects in different stages of disease. We evaluated a newly developed 6-month group-based multicomponent cognitive intervention in a randomized controlled pilot study on subjects with amnestic mild cognitive impairment (aMCI) and mild AD patients. Forty-three subjects with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 66 publications
3
127
0
11
Order By: Relevance
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…49,51,53 All of the studies reported on attrition to the programme, although the intention-to-treat analysis plan was described in only two. 6,51 Given the nature of the condition and the age of the participants, attrition in several studies was remarkably small, with zero attrition recorded in six studies [48][49][50]52,59,60 out of 180 participants. The largest attrition rate was reported in the study by Wallis et al, 63 in which there was 39% attrition in the group of participants with dementia.…”
Section: Figurementioning
confidence: 99%
“…47 Two reviewers independently assessed eligibility. Of the 94 references, nine studies met the inclusion criteria [48][49][50][51][52][53][54][55] and were included in the analysis. Three recent studies were left awaiting classification.…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, psychoeducational elements e.g. with topics related to healthy cognitive aging including risk and protective factors, mechanisms of cognitive functions, or cognitive strategies are part of some cognitive group trainings which were developed for elderly people with or without cognitive dysfunctions [15] [16] [17] [18], but are usually not implemented in digital trainings. However, standardized CCT programs tailored for elderly people could be especially useful, as they would constitute a form of "guided" training [11] for this group.…”
Section: Introductionmentioning
confidence: 99%